Relationship between periodontitis and psoriasis: A two‐sample Mendelian randomization study. (1st April 2022) - Baurecht, Hansjörg; Freuer, Dennis; Welker, Christine; Tsoi, Lam C.; Elder, James T.; Ehmke, Benjamin; Leitzmann, Michael F.; Holtfreter, Birte; Baumeister, Sebastian‐Edgar
Abstract: Aim: Observational research suggests that periodontitis affects psoriasis. However, observational studies are prone to reverse causation and confounding, which hampers drawing causal conclusions and the effect direction. We applied the Mendelian randomization (MR) method to comprehensively assess the potential bi‐directional association between periodontitis and psoriasis. Materials and Methods: We used genetic instruments from the largest available genome‐wide association study of European descent for periodontitis (17, 353 cases, 28, 210 controls) to investigate the relationship with psoriasis (13, 229 cases, 21, 543 controls), and vice versa. Causal Analysis Using Summary Effect (CAUSE) estimates and inverse variance‐weighted (IVW) MR analyses were used for the primary analysis. Robust MR approaches were used for sensitivity analyses. Results: Both univariable methods, CAUSE and IVW MR analyses, did not reveal any impact of periodontitis on psoriasis (CAUSE odds ratio [OR] = 1.00, p = 1.00; IVW OR = 1.02, p = .6247), or vice versa (CAUSE OR = 1.01, p = .5135; IVW OR = 1.00, p = .7070). The null association was corroborated by pleiotropy‐robust methods with ORs close to 1 and p ‐values >.59. Overall, MR analyses did not suggest any effect of periodontitis on psoriasis. Similarly, there was no evidence to support an effect of psoriasis on periodontitis. Conclusions: Within the limitations of this MR study, the outcomes supported neither periodontitis affecting psoriasis nor psoriasis affecting periodontitis.